KARAKTERISTIK DAN STATUS GIZI ANAK UMUR 6-24 BULAN DI DAERAH KUMUH PERKOTAAN JAKARTA - Azrimaidaliza Azrimaidaliza (Jurnal Kesehatan Masyarakat Andalas, 2009)
Nutrition and Health Surveillance System (NSS) year 1999 - 2003 shows prevalence of underweight (weightfor age < -2 SD from NCHS media) was very high, that is above 30% on infant at rural and urban slum areas. An underweight prevalence at urban slum areas is higher than rural slum areas, especially is at urban slum area of Jakarta. In this area prevalence of underweight children 12 -23 months of age (June-September 2003) was 42%. This study aims at know the characteristic of children 6 until 24 months and factors related with their nutrient status in urban slum of Jakarta. This study was using NSS secondary data period of June-September 2003. The study results show that child 18-24 months of age have risk in having underweight 2, 8 times compared with child 12-1 7 months and child 6-11 months. Moreover, child with birth weight < 2,5 kilo (OR = 2,9 times) and birth from mother with Body Mass Index d" 18,5 (OR = 1,64 times) and upper arm circumference < 23,5 cm ( OR = 1,48 times) have bigger risk in having underweight. The cause was cumulative effect of being underweight along life. Beside that, child with low birth weight record is difficult to catch up their growth if they do not get a good caring, especially adequate food.